International Association of Dental Traumatology guidelines for the management of traumatic dental injuries: 2. Avulsion of permanent teeth. Issue 4 (13th June 2020) - Fouad, Ashraf F.; Abbott, Paul V.; Tsilingaridis, Georgios; Cohenca, Nestor; Lauridsen, Eva; Bourguignon, Cecilia; O'Connell, Anne; Flores, Marie Therese; Day, Peter F.; Hicks, Lamar; Andreasen, Jens Ove; Cehreli, Zafer C.; et al.
Abstract: Avulsion of permanent teeth is one of the most serious dental injuries. Prompt and correct emergency management is essential for attaining the best outcome after this injury. The International Association of Dental Traumatology (IADT) has developed these Guidelines as a consensus statement after a comprehensive review of the dental literature and working group discussions. It represents the current best evidence and practice based on that literature search and expert opinions. Experienced researchers and clinicians from various specialties and the general dentistry community were included in the working group. In cases where the published data did not appear conclusive, recommendations were based on consensus opinions or majority decisions of the working group. They were then reviewed and approved by the members of the IADT Board of Directors. The purpose of these Guidelines is to provide clinicians with the most widely accepted and scientifically plausible approaches for the immediate or urgent care of avulsed permanent teeth. The IADT does not, and cannot, guarantee favorable outcomes from adherence to the Guidelines. However, the IADT believes that their application can maximize the probability of favorable outcomes.